57.6k views
2 votes
What is the difference? (x+5)/(x+2)-(x+1)/(X^2+2x)

2 Answers

2 votes

(x+5)/(x+2) - (x+1)/(x^(2)+2x ) = (x^(2)+4x-1 )/( x^(2) +2x)
User Alexander Fuchs
by
5.1k points
4 votes

Answer:


\text{The difference is }(x^2+4x-1)/(x(x+2))

Explanation:

Given two expression, we have to find the difference of these two.


(x+5)/(x+2)-(x+1)/(x^2+2x)


=(x+5)/(x+2)-(x+1)/(x(x+2))


\text{Taking (x+2) common from the denominator }


=(1)/(x+2)((x+5)-(x+1)/(x)


=(1)/(x+2)((x(x+5)-(x+1))/(x))


=(1)/(x+2)((x^2+5x-x-1)/(x)


=(1)/(x+2)((x^2+4x-1)/(x))


=(x^2+4x-1)/(x(x+2))

which is required difference.

User VizFlux
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.